2022
DOI: 10.12746/swrccc.v10i42.977
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of evidence-based medicine instruction in medical school clerkships

Abstract: Introduction: The instruction of evidence-based medicine (EBM) in health sciences institutions is increasing. As used in medical schools, it looks to implement research-oriented approaches to clinical interventions and further develop the skills of medical students in evaluating and applying research.Objectives: This study aimed to identify the effectiveness of an evidence-based medicine clerkship offered at a single institution to third-year medical students during their surgery rotation. Methods: Two surveys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The findings of this study show that the majority of the participated physiotherapy professionals in Sri Lanka have gone through an introduction to EBP during their academic programme. This is a positive sign as it improves the physiotherapists' residents' skills in critical appraisal, as mentioned by Dan Stuart et al 2022 [10]. On the other hand, researchers found that although most physiotherapy providers are conscious of the importance of EBP in their clinical practice, they might encounter several barriers when pursuing it.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The findings of this study show that the majority of the participated physiotherapy professionals in Sri Lanka have gone through an introduction to EBP during their academic programme. This is a positive sign as it improves the physiotherapists' residents' skills in critical appraisal, as mentioned by Dan Stuart et al 2022 [10]. On the other hand, researchers found that although most physiotherapy providers are conscious of the importance of EBP in their clinical practice, they might encounter several barriers when pursuing it.…”
Section: Discussionmentioning
confidence: 94%
“…There were five questions in that part, and those were individually scored as 0 (strongly disagree), 1 (disagree), 2 (neutral), 3 (agree), and 4 (strongly agree) [4]. Based on the sum of the marks obtained for those questions, subjects were categorized as poor (0-6), average (7)(8)(9)(10)(11)(12)(13) and good (14-20) knowledge [4]. Under the attitudes part, all participants were rated according to the answers to individual questions.…”
Section: Discussionmentioning
confidence: 99%